PENGARUH KEPEMIMPINAN, PENDIDIKAN DAN PELATIHAN TERHADAP EFEKTIVITAS ORGANISASI MELALUI KOMPETENSI PADA PEGAWAI NEGERI SIPIL DI BIRO UMUM DAN DINAS PENDAPATAN DAERAH PROVINSI RIAU - Oktaviana, Suci; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2017)
The research held in public service institution under the government of RiauProvince. The aim is to know the direct and indirect influence of leadership andeducation and training to organizational effectiveness through competency as themediating variable. Population are public employees in Biro Umum and DinasPendapatan Daerah of Riau Province which consist of 254 employees. Samples takenby Slovin formulation that consists of 167 selected employees and sectionally clustered.Variables used are leadership and education and training as independent,organizational effectiveness as dependent and competency as the mediating variable.Data analyzed by using structural equation model which is processed by Amos 20. Thestudy reveals that directly leadership has no significant impact to organizationaleffectiveness. Competency, however, can mediate the positve impact of leadership toorganizational effectiveness. On the other hand, organizational culture has either director indirect impact to organizational effectiveness that mediated by competency. Amongall, competency has the biggest impact to organizational effectiveness compared toleadership or education and training. The optimalization of leadership along witheducation and training are recommended in order to enhance employeeâs competencyand organizational effectiveness.